2022
DOI: 10.1186/s12909-022-03156-6
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and future plans of the final year students in a Chinese dental school

Abstract: Background Understanding dental students’ future career choice and motivation could provide beneficial references for both educators and students, but there were few studies on students in a Chinese dental school. The study aimed to investigate Chinese final year dental students’ the short-term and long-term plans, motivations, and identify the influence of gender on the future plans. Methods A total of 265 final year dental school students of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…8 Similar findings have been reported in other studies where, for example, a higher desire to specialise was seen among Chinese and Nigerian dentists due to the perceived associated better financial returns when compared to a lower desire among Japanese, Australian and New Zealand students whose motivation in the profession was to help people and intellectual stimulation. 6,9,18,19 Contrary to findings in this study, some countries such as Saudi Arabia 20 and Japan 6 have reported influence by family members as a key factor determining choice of career in dentistry. The preference for pediatric dentistry by females more than males is consistent with a number of studies such as one in the UK.…”
Section: Discussioncontrasting
confidence: 86%
“…8 Similar findings have been reported in other studies where, for example, a higher desire to specialise was seen among Chinese and Nigerian dentists due to the perceived associated better financial returns when compared to a lower desire among Japanese, Australian and New Zealand students whose motivation in the profession was to help people and intellectual stimulation. 6,9,18,19 Contrary to findings in this study, some countries such as Saudi Arabia 20 and Japan 6 have reported influence by family members as a key factor determining choice of career in dentistry. The preference for pediatric dentistry by females more than males is consistent with a number of studies such as one in the UK.…”
Section: Discussioncontrasting
confidence: 86%
“…This study is done to document the motivation levels of dental students and house officers in LMDC and their choice of field after graduation. There is a significantly higher number of female participants in the current study reflecting the higher ratio of 12,13,14 females choosing dentistry as a profession. However the responses recorded did not show a significant difference in career choices and reasons for choosing any specific field are same for both genders.…”
Section: Discussionmentioning
confidence: 69%
“…There are 3 main career choices for dental graduates in mainland China: (1) to be a general dentist, who works mainly in county-level medical institutions or urban private dental clinics; (2) to pursue further training to become a specialist by completing a clinical dental master's degree program; and (3) to work as teaching or academic staff in a university or college by completing an academic master's degree program and sometimes a PhD degree is required. It should be pointed out that a national standardized residency training system was established in mainland China in 2014 (27).…”
Section: Mainland Chinamentioning
confidence: 99%
“…Dental graduates in different places report a variety of motivations and plans for career development. In mainland China, according to a survey conducted in 2022, a majority of dental graduates (88%) decided to pursue postgraduate degrees to increase their competitiveness in finding better jobs ( 2 ). Three favourite disciplines ranked by students were prosthodontics, oral surgery, and orthodontics ( 3 ).…”
Section: Introductionmentioning
confidence: 99%